PERBANKAN SYARIAH DALAM KEWIRAUSAHAAN: PENGARUH KURSUS PEMBELAJARAN KEWIRAUSAHAAN TERHADAP KEMAMPUAN ALUMNI - Sari, Purnama; Aminah, Rika (Journal Of Sharia Banking, 2023)
The problem in this research is motivated by the large number of unemployed graduates printed by tertiary institutions, including alumni of Islamic banking study programs.  Many college graduates have the mindset of job seekers not job creators and do not understand and are able to manage a business and there are still doubts about starting a business indicating that the ability to manage a business or expertise has not been fully formed so the formulation of the problem in this study is whether there is influence  learning entrepreneurship courses on the ability of alumni of Islamic banking in entrepreneurship and aims to determine the effect of learning entrepreneurship courses on the ability of alumni of Islamic banking in entrepreneurship.  The theory in this study relates to the field of entrepreneurship.  In this regard, the approach taken is theories related to learning entrepreneurship courses, indicators of entrepreneurship learning, entrepreneurial abilities and indicators in entrepreneurship.  This research is a quantitative research, data sources used are primary and secondary data, data analysis used is validity test, reliability test, basic assumption test (normality test, linearity test), hypothesis test (coefficient of determination test (R²), partial test  (t) and simple linear regression test using a statistical tool, namely SPSS version 23. Based on the results of the t test research on the Entrepreneurship Course Learning variable has an effect on the Ability of Islamic Banking Alumni in Entrepreneurship, this is evidenced by a significance value of 0.1 with 0.000  0.1, then Ha is accepted then the results of a simple linear regression analysis of the variable learning entrepreneurship courses with a constant value of 0.684 and the coefficient value of the variable learning entrepreneurship courses is 0.684.